Need to know : a novel - Cleveland, Karen (Ballantine Books, 2018)
"Vivian Miller is a dedicated CIA counterintelligence analyst assigned to uncover the leaders of Russian sleeper cells in the United States. On track for a much-needed promotion, she's developed a system for identifying Russian agents, seemingly normal people living in plain sight. After accessing the computer of a potential Russian operative, Vivian stumbles on a secret dossier of deep-cover agents within America's borders. A few clicks later, everything that matters to her--her job, her husband, even her four children--are threatened. Vivian has vowed to defend her country against all enemies, foreign and domestic. But now she's facing impossible choices. Torn between loyalty and betrayal, allegiance and treason, love and suspicion, who can she trust?"--